Raskólnikov e Meursault : um diálogo absurdo - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This Course Conclusion Work promotes a comparison between the main characters (Raskólnikov and Meursault) of the works Crime and Punishment, by the Russian writer Fiódor Dostoiévski, and The Stranger, by the Franco-Algerian writer Albert Camus. Based on the concept of Comparative Literature, the comparison between the characters occurs in order to analyze the conduct, the world view, and the reflections of Raskólnikov and Meursault, discussing the internal universe of the works and the influence of the context on the actions of the protagonists. , aiming at an approximation between the extraordinary man of Fyodor Dostoevsky and the absurd man, of Albert Camus. Thus, it was possible to observe how the characters behave in the face of the Absurdity of existence, a philosophical concept used by Albert Camus, and how much the context interfered with the construction of the characters. We conclude that the extraordinary man and the absurd man dialogue insofar as they both address issues related to the concept of nihilism, but Crime and Punishment and its protagonist are a denunciation of Dostoevsky against Russian nihilism, while The Stranger, from the figure of Meursault and his indifference, denounces the 20th century nihilism that, in Camus' view, promoted genocides and a series of totalitarian regimes in Europe, thus having a difference in the authors' conception of nihilism, from concepts of nihilism explored by Joseph Frank in his work, which consists of a vast biography of Dostoevsky, and also by Albert Camus in two of his essays: The Myth of Sisyphus and The Revolted Man.
Keywords: Comparação; Literatura; Absurdo; Niilismo; Comparison; Literature; Absurd; CNPQ::LINGUISTICA, LETRAS E ARTES